Calculated Optimized Structure and Geometric Analysis of Oxygenated Fuel Additives: Alcohols and Ethers - Gurkan Aydin, S.; Polat, O.; Ozgen, A.; Turali, E. (Engineering, Technology & Applied Science Research, 2020)
Oxygenated fuel additives are added to gasoline in order to reduce the gases released from vehicle engines, to increase the octane number, and to expand the use of renewable resources. In this study, molecular and geometric analysis of oxygenated fuel additives was conducted theoretically and the energy values of optimized structures were calculated. The effect of molecular energy and the bond structure between C, H and O on the chemical and physical properties of some oxygen fuel additives were investigated. The obtained results will form the basis for future studies in obtaining more environmentally friendly fuels.